CLINICAL AND PATHOMORPHOLOGICAL MANIFESTATIONS OF RESPIRATORY SYNCYTIAL VIRUS INFECTION. CASE REPORT - I. V. Babachenko; V. E. Karev; K. V. Evdokimov (Журнал инфектологии)
On the example of clinical observation of severe respiratory syncytial virus (RSV) infection, which occurred with the development of a specific pneumonia complicated by acute respiratory distress-syndrome and disseminated intravascular coagulation syndrome, which caused a lethal outcome in the non-term (33-34 weeks gestation) child of two months of life, the clinical and pathomorphological features of the disease are shown. Immunomorphologic study after death allowed to demonstrate the most important stages of respiratory syncytial viral infection pathogenesis and to specify reasons of long-term airway obstruction, caused by complicated respiratory syncytial viral infection. It was indicated, that bronchial obstruction may be caused by qualitative changes of epithelial lumen of different bronchi, such as direct cytophatic effect of respiratory virus or reactive changes of lumen in the form of basal squamous cell differentiation of epithelial lumen and poor regeneration of respiratory epithelium in the later stages of the disease.